Challenges of Students' Oral Presentations and the Teacher's Role in Addressing - Tolipova Shaxnoza Shuxratovna (Global Scientific Publishing, 2024)
This article focuses on the importance of student's oral presentation and difficulties, as well as the role of the teacher in solving them
Keywords: oral speech; difficulties; solution